A 2-center comparison of maxillary incisor positioning with non-extraction, 2-maxillary premolar and 4-premolar extractions for Class II treatment. Issue 4 (December 2015) - Janson, Guilherme; Simão, Tassiana Mesquita; Barros, Sérgio Estelita; Tompson, Bryan D.; Freitas, Karina
Abstract: Purpose: The purpose of this study was to evaluate the maxillary incisors position and soft-tissue characteristics of Class II, division 1 patients treated with non-extraction, 2-maxillary and 4-premolar extraction protocols. Materials and methods: The sample of 120 subjects was divided into four groups. The first three treated groups presented Class II, division 1 malocclusion patients. G1 comprised 30 patients (14.95 years), and was treated without extraction. G2 comprised 30 patients (15.28 years), treated with extraction of 2-maxillary premolars. G3 consisted of 30 patients (15.55 years), treated with extraction of 4-premolars, and G4 included 30 individuals (14.93 years) with normal occlusion. The occlusal features of the treated groups were evaluated by the Peer Assessment Rating (PAR) index and the cephalometric characteristics were compared with ANOVA. Results: The maxillary incisors were similarly positioned among the treated groups at the end of treatment. However, they were more upright in G2 and G3 than in the control group (G4). The hard- and soft-tissue cephalometric characteristics were similar in all groups. Conclusion: Class II treatment conducted non-extraction, with 2-maxillary and with 4-premolar extraction protocols showed similar effects on final maxillary incisors positioning and nasolabial angle. In general, the 4-premolar extraction protocol was potentially more retrusive, but the dentofacial differences were slight and not statistically significant.